Pendampingan Sertifikasi Halal Melalui Program Sehati Bagi UMKM di Dusun Wareng Desa Kepek Kecamatan Saptosari - Fika Farhatur Robbi; Maharani, Annida; Jefriyanto Budikafa, Muhammad (Jurnal Riset dan Pengabdian Masyarakat, 2024)
Halal certification is one of the requirements for importing, distributing and trading a product in Indonesian territory. In Wareng hamlet, there is one MSME group and two MSMEs that were formed individually, but their products are not yet labeled halal and do not have a business license registration number. The reason why Wareng hamlet MSMEs have not received halal certification for their products is a lack of knowledge and understanding regarding halal certification obligations. This year the government opened registration for the Halal certification program, namely the SEHATI Program. This service activity aims to provide outreach to increase knowledge and understanding regarding halal certification obligations for a product. Apart from that, this service provides assistance in applying for halal certification through the SEHATI program. This service method uses the Asset Based Community Development (ABCD) approach which focuses on asset-focused community development, namely developing Wareng hamlet MSME products so that their products receive halal certification. Results: MSMEs Wareng Hamlet have become more aware of the obligations of halal certification and have begun to apply for halal certification through the SEHATI program and currently the halal certification stage is in the process, taking two months.